Spatial variation of land and real estate prices in Karkh center shops and their spatial relationships with urban land uses (Journal of the College of Basic Education, 2022)
The choice of this topic (prices of land and real estate in the shops of the Karkh Center) came in line with the scientific nature of the study because it reflects a geographical, economic and urban aspect on the one hand, and meets the need of society, including the population and the state, represented in controlling the spatial behavior of this phenomenon on the other hand.The problem of the study was represented by the spatial variation of land and real estate prices in the Karkh center shops. And its hypothesis that sought to explain this spatial variance with its spatial relationships with urban land uses (governmental, industrial, residential, commercial, community services, empty spaces, transportation and main streets).